Performance-based comparative study of commercial polymeric nanofiltration membranes for ionic retention from synthetic water - Qadir, D. (Springer Science and Business Media Deutschland GmbH, 2022)
Freshwater has gained the status of holy grail recently due to rapid industrial and population growth. Many studies are carried out to address this critical issue, and modern technologies are also developed. This study evaluated the properties and performance of commercial membranes (NF270, NP030, and NT103) under similar feed conditions. Four salts (NaCl, MgCl2, CaCl2, SnCl2) of monovalent (Na+) and divalent type cations (Ca2+, Mg2+, Sn2+) with common chloride ion (Clâ) were selected for performance evaluation of these membranes. The characterization results showed an asymmetric structure with three distinct layers and hydrophilic surfaces with negative surface charges. The NF270 and NP030 were found to have a smoother surface than NT103 membranes with NP030 having highly negatively charged surface (â 18.9Â mV). The performance analysis showed the order of pure water flux as: NF270 > NT103 > NP030. The rejection analysis showed that the NF270 membrane had 99.9 tin ion rejection for 100Â ppm solution at 10Â bar pressure. This work contributes to rarely seen literature about the comprehensive comparison of commercial membranes for emerging pollutant such as tin ion, which is becoming a serious threat not only to the environment but also to humans due to its excessive use in plastic, paints and food industry. Â© 2022, The Author(s) under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University.